Photophysical, electrochemical, and mesomorphic properties of a liquid-crystalline [60]fullerene-peralkylated ferrocene dyad - Campidelli, Stephane; Severac, Marjorie; Scanu, David; Deschenaux, Robert; Vazquez, Ester; Milic, Dragana; Prato, Maurizio; Carano, Maurizio; Marcaccio, Massimo; Paolucci, Francesco; Rahman, Aminur; Guldi, Dirk Michael (Journal of Materials Chemistry, 2008)
Two fullerene-peralkylated ferrocene derivatives were synthesized: (1) a liquid-crystalline dyad (compound 1) was obtained by introduction of nonamethyl ferrocene into a liquid-crystalline fullerene derivative and (2) a reference compound (compound 2) was synthesized by attachment of nonamethyl ferrocene to a fulleropyrrolidine. The liquid-crystalline dyad displayed an enantiotropic smectic A phase from 57 to 155 °C. Oxidation and reduction processes were investigated by cyclic voltammetry, and were in agreement with the electrochemical characteristics of the redox-active units (peralkylated ferrocene, fullerene, dendrimer). Photoinduced electron transfer from ferrocene derivative to fullerene was identified. © The Royal Society of Chemistry.